2005
DOI: 10.3952/lithjphys.45209
|View full text |Cite
|
Sign up to set email alerts
|

NonlinearIVcharacteristics in polyaniline due to phonon-assisted tunnelling

Abstract: Non-linear temperature-dependent current-voltage (I-V ) characteristics of an organic polyaniline (PAN) thin films diodes measured by Kieffel et al. (Synth. Met. 135-136, 325-326 (2003)) is explained on the basis of phonon-assisted tunnelling initiated by electrical field. 87-91 (2003) are also explained on the basis of the free charge carrier generation tunnelling mechanism. From the fit of the experimental data with the present model the density of localised states which take part in the current flow is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…This value of mass was found to be preferable for explanation of temperature-dependent non-linear current-voltage characteristics in PANI films [16]. At temperatures T4100 K the value of phonon energy of 12 meV was shown [13] to be workable.…”
Section: Comparison and Discussionmentioning
confidence: 96%
“…This value of mass was found to be preferable for explanation of temperature-dependent non-linear current-voltage characteristics in PANI films [16]. At temperatures T4100 K the value of phonon energy of 12 meV was shown [13] to be workable.…”
Section: Comparison and Discussionmentioning
confidence: 96%
“…, wherehω is the phonon energy, ε T is the energy depth of the center, e is the electron charge, and a is the electron-phonon interaction constant (a = Γ 2 0 /8(hω) 2 ).This relatively simple expression was proved to be valid to describe not only the temperature-dependent current-voltage data in inorganic materials [10], but also in the case of π-conjugated organic conducting polymers [6][7][8]. Consequently, we will use this equation to explain the peculiarities of temperature-dependent current in polydiacetylene single crystals.…”
Section: Theory and A Comparison With Experimental Datamentioning
confidence: 99%
“…We argue that the temperature dependence of the conductivity in PDA crystals [3] as well as in DCH-PDA crystals measured by Elman et al [5] can be well described in terms of phononassisted tunnelling, as the charge carriers delocalization process. The temperatureBrought to you by | MIT Libraries Authenticated Download Date | 5/11/18 3:39 AM dependent tunnelling process has been also used for explanation of the temperaturedependent of I − V characteristics in some polymers [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we focus on the data of the crossover from a non-metallic to metallic sign of conductivity at temperatures between 4 K and 200 K and show that the trend of conductivity with temperature is well accounted for by the PhAT model similar to that used for polymers [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A plenty of mechanisms used for explanation of the temperature dependence of current peculiarities in SWCNT networks implies that the conduction mechanism in these materials is not fully understood. Recently we have shown that the temperature-dependent conductivity of nanotubular polyaniline [18] and other polymers [19,20] can be explained by a model based on a phonon-assisted tunnelling (PhAT), as a mechanism of free charge carriers generation. Since the PhAT theory predicts an absorption / emission of phonons in the process of carrier tunnelling, the variation of current / conductivity with temperature will be determined by the competition of the absorption and emission of phonons.…”
Section: Introductionmentioning
confidence: 99%